Palladium/Norbornene‐Catalyzed C−H Alkylation/Alkyne Insertion/Indole Dearomatization Domino Reaction: Assembly of Spiroindolenine‐Containing Pentacyclic Frameworks. Issue 18 (23rd March 2018) - Bai, Lu; Liu, Jingjing; Hu, Wenjie; Li, Kunyu; Wang, Yaoyu; Luan, Xinjun
Abstract: Reported is a highly chemoselective intermolecular annulation of indole‐based biaryls with bromoalkyl alkynes by using palladium/norbornene (Pd/NBE) cooperative catalysis. This reaction is realized through a sequence of Catellani‐type C−H alkylation, alkyne insertion, and indole dearomatization, by forming two C(sp 2 )−C(sp 3 ) and one C(sp 2 )−C(sp 2 ) bonds in a single chemical operation, thus providing a diverse range of pentacyclic molecules, containing a spiroindolenine fragment, in good yields with excellent functional‐group tolerance. Preliminary mechanistic studies reveal that C−H bond cleavage is likely involved in the rate‐determining step, and the indole dearomatization might take place through an olefin coordination/insertion and β‐hydride elimination Heck‐type pathway. Abstract : A sequence of three : A novel palladium/norbornene (NBE) catalyzed intermolecular annulation of indole‐derived aryl iodides with tethered bromoalkyl alkynes has been developed for the rapid construction of pentacyclic scaffolds containing a spiroindolenine fragment. This reaction was realized through a C−H alkylation, alkyne insertion, and indole dearomatization sequence.